A Dual Emissive Coumarin–urea Derivative with an Electron‐withdrawing Substituent in the Presence of Acetate Anion. (20th October 2019) - Shinoda, Tomoyuki; Nishimura, Yoshinobu; Arai, Tatsuo
Abstract: We investigated the fluorescent properties, including the excited‐state intermolecular proton transfer, of urea derivatives comprising a coumarin ring, which is a widely used fluorophore. We prepared two different coumarin–urea derivatives, 6CU and 7CU, which bear a urea‐based substituent at the 6 and 7 positions of a coumarin ring, respectively. In the presence of the acetate ion, 7CU showed additional tautomer fluorescence emission with respect to 6CU, indicating that tautomer formation depends on the positions of the urea‐based substituent on the coumarin ring. Thus, the resonance structures of urea derivatives might play an important role in the behavior of dual fluorescence, which is an important phenomenon applicable to photochemical anion sensing. Moreover, in order to further improve the fluorescence properties of the mentioned derivatives, a CF3 group was introduced in a phenyl ring opposite to a coumarin ring. The fluorescence quantum yield of 7CUCF3 thus synthesized was 65 times as large as that of 7CU, an observation that renders 7CUCF3 a suitable anion sensor candidate. The results of this study will contribute to the development of new molecular designs for highly fluorescent sensing. Abstract : Coumarin–urea derivatives showed significant differences in tautomer formation depending on the positions of a urea moiety substituted on the coumarin ring in the presence of acetate ion. Furthermore, the substitution of a CF3 group resulted in a remarkable improvement of its fluorescence quantum yield. These findings will contribute to new molecular design of highly fluorescent anion sensors.